Cooperative Networking towards Maritime Cyber Physical Systems. (2nd March 2016) - Yang, Tingting; Feng, Hailong; Yang, Chengming; Sun, Zhonghua; Yang, Jiadong; Sun, Fan; Deng, Ruilong; Su, Zhou
Abstract : An innovative paradigm named Cooperative Cognitive Maritime Cyber Physical Systems (CCMCPSs) is developed to achieve high-speed and low-cost communication services. The analysis of the available white space at sea, as well as the framework, is presented. Specifically, a bilevel game with two stages of PUs-to-SUs (primary users to secondary users) and SUs-to-SUs is proposed, to address the resource allocation issue of Decode-and-Forward (DF) relay mode with maximal-ratio combining (MRC) receiving mode in destination. Stackelberg game with priority is employed between PU and SUs, while a symmetrical system model is considered among SUs-to-SUs. The game theoretic procedure that converges to Nash equilibrium based on the utility and payoff function is illustrated. Simulation results demonstrate that our proposed strategy could effectively increase the throughput as well as the payoffs of the system.